A low-distortion multi-bit sigma–delta ADC with mismatch-shaping DACs for WLAN applications. Issue 1 (January 2015) - Li, Di; Yang, Yin-Tang; Shi, Zuo-Chen; Liu, Yang
Abstract A low-distortion feed-forward MASH24b-24b sigma–delta analog-to-digital converter (ADC) for wireless local area network (WLAN) applications was presented. The converter exhibits improved performances than the ADCs which have been presented to date by adding a feedback factor in the second stage and employing a 2nd-order noise-shaping dynamic element matching (DEM) scheme. The feedback factor induces a zero in the noise transfer function (NTF) and therefore improves the in-band signal to noise and distortion ratio (SNDR) of the modulator. The mismatch-shaping DEM was introduced and applied to the 4-bit DACs in this paper to improve the resolution and linearity of the ADC. Fabricated in a 0.18 μm CMOS process with single 1.8 V supply voltage, the converter achieves a peak SNDR of 85.4 dB over a 10 MHz bandwidth which implies an effective number of bits (ENOB) of 13.90-bit. The spurious free dynamic range (SFDR) is –94 dB for a 1.25 MHz@–6dBFS input signal at 160 MHz sampling frequency. The occupied area is 0.44 mm2 and dissipation power 23.4 mW.